MORAL LEARNING STRATEGIES AT MADRASAH MU'ALLIMAAT MUHAMMADIYAH YOGYAKARTA DURING THE COVID-19 PANDEMIC - Putri, Mutia Eka; Kistoro, Hanif Cahyo Adi; Muhliana, Syafira Intan; Sari, Prima Rosita (Idaarah: Jurnal Manajemen Pendidikan, 2023)
Moral material becomes an essential thing in education. During the Covid-19 pandemic, the education sector changed policy. Every teacher must determine learning strategies following existing conditions, especially moral teachers who must use the right approach to transfer knowledge and instill morals in students optimally. This research was conducted to describe the learning strategies applied by the moral teachers of Madrasah Mu'allimaat Muhammadiyah Yogyakarta and the accompanying constraints. The type of research used is qualitative research with a descriptive approach. This study used respondents consisting of seven people as informants, namely two moral teachers, the deputy director of the curriculum section, and four students of Madrasah Mu'allimaat Muhammadiyah Yogyakarta. Then, interviews and documentations were data collection techniques used by researchers—analysis of data processing using data reduction procedures, data presentation and conclusion. Based on the research results obtained, the learning strategy used by the moral teachers at Mu'allimaat Muhammadiyah Yogyakarta during the Covid-19 pandemic was expository and active learning. As for the obstacles faced, namely the limitations of space, time (class hours), resources (network and IT devices), and the need for more motivation of the students. Even though there were several obstacles, they could be handled/appropriately resolved. This research has limitations, including the difficulty of arranging interview schedules because it is hindered by semester holidays and the school is busy accepting new students. The recommendation from this study is that teachers must be more able to manage classes optimally, especially by using suitable approaches and strategies. With this research, it is hoped that it can become a reference and reference for further similar research.